2023
DOI: 10.3390/nu15092099
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Mediterranean Diet in Breast Cancer Survivorship: A Systematic Review and Meta-Analysis of Observational Studies and Randomised Controlled Trials

Abstract: Female breast cancer is the most frequently diagnosed cancer. The long-term survival rates for this disease have increased; however, the unique demand for high-quality healthcare to improve breast-cancer survivorship are commonly unmet. The Mediterranean diet (MD) is associated with reduced breast-cancer risk and various health-related benefits in the general population, but its effect on breast-cancer survivors remains uncertain. The objective of this systematic review and meta-analysis was to assess current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…In particular, a systematic review and meta-analysis of observational studies and randomized controlled trials has shown that high adherence to the MD is associated with a reduced risk of all-cause mortality among BCS [271].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, a systematic review and meta-analysis of observational studies and randomized controlled trials has shown that high adherence to the MD is associated with a reduced risk of all-cause mortality among BCS [271].…”
Section: Discussionmentioning
confidence: 99%
“…As regards BC, a high adherence to the MD is associated with benefits in terms of both prevention and improvement of clinical outcomes [271,278]. The combination of foods with nutraceutical properties and the richness in bioactive compounds of many typical foods of the MD such as fresh vegetables, fruit, and EVOO could exhibit multiple anticancer effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no specific diet has been proven to prevent cancer recurrence, the Mediterranean diet is an anti‐inflammatory and antioxidant plant‐based diet that consists of fruits, vegetables, nuts, legumes, and olive oil. Strict adherence to this diet, which limits alcohol, sweets, and red meat, has been shown to decrease breast cancer risk and improve health parameters 54 …”
Section: Screening and Management Of Systemic Therapy Treatment Side ...mentioning
confidence: 99%